2023
DOI: 10.1038/s41598-023-32296-y
|View full text |Cite
|
Sign up to set email alerts
|

Nano‑zinc enhances gene regulation of non‑specific immunity and antioxidative status to mitigate multiple stresses in fish

Abstract: The toxicity of ammonia surged with arsenic pollution and high temperature (34 °C). As climate change enhances the pollution in water bodies, however, the aquatic animals are drastically affected and extinct from nature. The present investigation aims to mitigate arsenic and ammonia toxicity and high-temperature stress (As + NH3 + T) using zinc nanoparticles (Zn-NPs) in Pangasianodon hypophthalmus. Zn-NPs were synthesized using fisheries waste to developing Zn-NPs diets. The four isonitrogenous and isocaloric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 106 publications
1
7
0
Order By: Relevance
“…Ibrahim et al [ 66 ] reported similar results after feeding the same levels of ZnONPs synthesized from Nelumbo nucifera to Nile tilapia for 84 days, and in tilapia-fed ZnONPs at 30 mg/kg for 12 weeks, where a significant increase in CAT and GPx was reported [ 26 ]. Increased activities of CAT, GST, and GPx were also evident in Pangasianodon hypophthalmus fed ZnNPs synthesized from fishery waste [ 5 ] and in beluga ( Huso huso ) fed chitosan-ZnONPs for 28 days Gharaei et al [ 72 ]. However, no significant difference in the activity of the MDA enzyme was found in the present study in either of the supplemented groups, which is consistent with the findings of Gharaei et al [ 72 ], suggesting that dietary BIO-ZnNPs did not induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ibrahim et al [ 66 ] reported similar results after feeding the same levels of ZnONPs synthesized from Nelumbo nucifera to Nile tilapia for 84 days, and in tilapia-fed ZnONPs at 30 mg/kg for 12 weeks, where a significant increase in CAT and GPx was reported [ 26 ]. Increased activities of CAT, GST, and GPx were also evident in Pangasianodon hypophthalmus fed ZnNPs synthesized from fishery waste [ 5 ] and in beluga ( Huso huso ) fed chitosan-ZnONPs for 28 days Gharaei et al [ 72 ]. However, no significant difference in the activity of the MDA enzyme was found in the present study in either of the supplemented groups, which is consistent with the findings of Gharaei et al [ 72 ], suggesting that dietary BIO-ZnNPs did not induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most abundant trace metals in fish obtained from water and/or diet through the gills and alimentary canal, and cannot be produced biologically [ 4 ]. Dietary Zn is essential for fish because it is involved in numerous metabolic pathways as a specific cofactor of several enzymatic reactions, a structural unit of non-enzymatic macromolecules, and an important component of body fluids [ 5 ]. Recently, dietary Zn has been reported to promote immuno-biochemical plasticity in fish and to provide protection against several stressors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline single cell gel electrophoresis/comet assay was applied for determination of DNA damage in kidney tissue using Ali et al 50 . with slight modification 51 . The slides coating and other procedure were followed the above method.…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia pollution originates from agricultural runoff and the decomposition of biological waste in aquatic systems, posing a significant threat to aquatic animals. Ammonia's toxicity arises as NH 4 + displaces K + and depolarizes neurons, leading to NMDA-type glutamate receptor activation, excessive Ca 2 + influx, and subsequent central nervous system cell death 19 , 20 . Total ammonia exists in two forms, ionized (NH 4 + ) and un-ionized (NH 3 ), with NH 3 diffusing through biological cell membranes and inducing toxicity 21 .…”
Section: Introductionmentioning
confidence: 99%